The development of self-esteem among school students - Yahaya, Azizi (2003)
Self-esteem is a positive or negative orientation toward oneself. An overall evaluation of one’s worth or value. People who are motivated will have high esteem, and having it indicates positive self-regard, not egotism. In general, the more positive your self-esteem, the more successful you will be at dealing with life. There are a number of things which causes lack of selfesteem too. Negative self-esteem is related to low self-confidence, insecurity, nderachievement, anxiety, depression, acting out behaviour,sleep problem and being alone (Yarnell). It is important for all teachers and parents to understand how their children’s self-esteem is created and maintained as well as how it can be diminished. The development of selfesteem plays an important role in helping individuals to make adjustment about their self-worth and competence. The primary contributor to self esteem changes according to the stages they are in. Whatever the ability of the child is, the parents or the teachers must know ways to communicate andthereby build the self-esteem in the child. To steer the thoughts of thestudents in the right direction, teachers have to train them to respectindividuals and not be influenced by peers’ pressure or the masses. Competence builds the ego, success begets success, being loved is to give love and you command the respect of others if you have the self-esteem